The Relationship of Young Women's Knowledge and Attitudes About the Physical Changes of Puberty with Self-Confidence - Nurlailis Saadah; Anindya Amru Damayanti; Teta Puji Rahayu; Budi Joko Santosa; Shaik Balkhis Banu (International Journal of Advanced Health Science and Technology, 2022)
There are still many teenagers who do not know about the physical changes of puberty, so it can affect their confidence. Adolescents must have good self-confidence so that they can help carry out their developmental tasks, in the formation of self-image or identity in adolescents, and the process of adjusting themselves to their social, both to peers and people around them. This study aims to find out the relationship between knowledge and attitudes of adolescent girls about the physical changes of puberty with self-confidence. This research method is observational with a cross-sectional approach. Sampling uses simple random sampling. Independent variables are knowledge and attitudes, while dependent variables are self-confidence. Data collection using questionnaires. The analysis using the Chi-Square test resulted from 71 respondents obtained students who had less knowledge as many as 53 students, had negative attitudes as many as 46 students, and almost all students had low self-confidence as many as 52 students. The results of the analysis of the relationship of knowledge with self-confidence value p value = 0.010 and attitude relationship with self-confidence value p value = 0.003. In conclusion, there is a significant relationship between the knowledge and attitude of young women about the physical changes of puberty with self-confidence in MTs student Ar-Rohman Tegalrejo Semen. It is hoped that school teachers can provide explanations about the physical changes that occur in young women, so that students are better prepared for the changes that occur, and can maintain and improve their reproductive health;